Preparation of Platinum Nanoparticles in Solution of Polyvinyl Pyrrolydone (PVP) by Laser Ablation Method - Binh, Nguyen The; Thanh, Nguyen Dinh; Dong, Nguyen Quang; Trinh, Nguyen Thi (VNU Journal of Science: Mathematics - Physics; Vol 30 No 2, 2014)
Abstract: Using Nd:YAG laser we studied to produce platinum nanoparticles (PtNPs)  in solution of polyvinyl pyrrolidone (C 6 H 9 NO) n (PVP) by laser ablation method. The influence of average laser power, laser irradiation time, laser wave length and concentration of PVP solution in water on morphology, size distribution of PtNPs was investigated. The mean diameter of the PtNPs in 0.01M PVP solution was of 9 nm. The results on an optimum laser ablation process for preparation of PtNPs in PVP solution were discussed in this paper. Keywords: Laser ablation, plasmon resonance, nanoparticle, second harmonic .